Partie i fakcje w schyłkowym okresie rządów Augusta III Sasa - Kuras, Katarzyna (Przegląd Nauk Historycznych, 2013)
The objective of the article is to analyze the parties and factions existing in the final period of Augustus’ III Wettin reign and to discover the appropriate meaning of the terms „party” and „faction” in this period. It is journalism or „occasional writings” that dominates in the group of the sources used as a base of information about the divisions existing on the political scene and „principles” exploited to make struggle between parties more dynamic. It turns out that the existence of parties was not guaranteed by the person of powerful leader, structures or parties’ programme. Much more important were „principles” or „slogans” and current opportunistic fight on the domestic forum, during which (e.g. in the years 1762–1763) significant changes on the political scene were introduced. Consequently, both political divisions and parties’ affiliations were dynamic and heterogeneous, related to promoted slogans, possible financial benefits, not the programme. As a result, the parties existing in this period in the Polish-Lithuanian Commonwealth: the Familia, republican party and court party, were rather platforms of agreement of various factions than compact, homogeneous formations.